Between the divine and the demonic: Dostoyevsky's 'Demons' and 'The Brothers Karamazov' as portraits of Russian Christian orthodoxy, identity and existentialism - Mahim, Saif Mahmood (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2024.